Estradiol-17β Injection Induces Ovulation in Llamas - Bianchi, Carolina P.; Benavente, Micaela A.; Viviani, Florencia; Gallelli, María F.; Aba, Marcelo A. (Frontiers in Veterinary Science, 2020)
This study aimed to investigate the effect of three different doses of estradiol-17β on ovulation and subsequent luteal development and function in llamas. Twenty-three llamas were examined daily by transrectal ultrasonography until the detection of an ovulatory follicle (≥8 mm). Thereafter, animals were divided into five groups: Control (n = 3; treated with 1.6 ml of saline solution), GnRH group (n = 6, treated with an intravenous injection of 8.4 μg Buserelin), and estradiol groups that received 0.6 mg (E1, n = 4), 1 mg (E2, n = 4), or 1.6 mg (E3, n = 6) of estradiol-17β intravenously. Detection of ovulation was based on ultrasonographic visualization of disappearance of the largest follicle and subsequent presence of a newly formed corpus luteum (CL) and progesterone concentration exceeding 1 ng ml−1. Daily blood samples were collected to determine plasma progesterone concentration. Ovulation rate was 0% for control and E1 groups, 25% for E2 group, and 100% for GnRH and E3 groups. Differences in the mean CL diameter between GnRH and E3 groups were not statistically significant. Plasma progesterone concentration was similar between groups during the different days in ovulated animals. However, the day that the plasma progesterone concentration was above 1 ng ml−1 and the day that the highest plasma progesterone concentration was achieved differed among E3 and GnRH groups, occurring later in females treated with estradiol. In conclusion, an injection of estradiol-17β is capable of inducing ovulation in llamas and the response depends on the dose used. Most of the animals required the highest tested dose (1.6 mg) to induce the ovulatory process. Although the CL diameter in females induced to ovulate with estradiol was similar to that in llamas induced to ovulate with a GnRH analog, the rise in plasma progesterone concentration above 1 ng ml−1 and the peak progesterone concentration were attained 1 day later in the estradiol treated females.